A Study of the Tenth Grade Students’ NarrativeWriting Achievement at SMAN 2 Jember - Lazuardin, Zenela; Ariani, Musli; Widja Putra, Bambang Arya (EFL Education Journal, 2016)
Abstract: This research was intended to describe the tenth grade students’ narrativewriting achievement at SMAN 2 Jember. The area and subjects of this researchwere chosen purposively by using purposive method. The research design wasdescriptive study. The research data were obtained by test, interview, anddocumentation. Based on the research finding dealing with the result of the tenthgrade students’ narrative writing achievement at SMAN 2 Jember, it was found thatthere were 2 students (5,13%) who were categorized as excellent, 13 students(33,33%) who were categorized very good, 12 students (30,77%) who werecategorized good, 12 students (30,77%) who were categorized as average, and nostudent (0%) who were categorized fair, poor, and very poor. This means that thetenth grade students’ narrative writing achievement at SMAN 2 Jember wascategorized good.Keywords: descriptive study, tenth grade students, narrative writing achievement.